The Role of Sundanese Parents In Ciptarasa-Ciptagelar Community on Ethnoparenting - Marina Trie Ramadhany Gunawan; Irfan Ansori; Fatima Rahma (SEAMEO CECCEP, 2024)
Parenting in early childhood is very dependent on the values of parenting given by parents. Parenting values are often full of culture and ethnicity from where the child's parents come from. The background of parenting values ​​possessed by parents provides different parenting patterns and outcomes for each child. The parenting process certainly involves fathers and mothers who play quite a big role. This research aims to reveal and describe the role of fathers and mothers in Ethnoparenting in the Sundanese Ciptarasa Ciptagelar Tribe. The data findings in this research were obtained through qualitative research methods with an ethnographic focus approach. This research succeeded in showing that the role of fathers and mothers in Ethnoparenting in the Sundanese Ciptarasa Ciptagelar Tribe is that parents play a role in domestic work, parents also play a role in implementing children's obligations and rights, apart from that parents also play a role in parenting which teaches character education to children.